FUNGSI KEPALA DESA DALAM MENYELENGGARAKAN PEMBANGUNAN DESA DI DESA BIPOLO DAN DESA OETETA, KECAMATAN SULAMU KABUPATEN KUPANG MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Naben, Empi Adriana; Yohanes, Saryono; Tupen, Rafael Rape (Petitum Law Journal, 2024)
Based on Law No. 6 of 2014 concerning Villages, Article 1 paragraph (2) states that "Village Government is the organizer of government affairs and the interests of local communities in the government system of the Unitary State of the Republic of Indonesia. The Village Government is the Village Head or what is referred to by another name, assisted by Village officials as the organizing element of the Village Government." The problems faced include, among other things, the function of the village head in carrying out village development in Bipolo Village and Oeteta Village must increase enthusiasm, and encourage the community in carrying out village development to involve more of the entire Bipolo Village community and Oeteta Village community in development activities. And provide outreach to the community that the community also has a role to be involved in the implementation of village development. This research aims to find out the function of the village head in carrying out village development in Bipolo Village and Oeteta Village and to find out the factors inhibiting the function of the Village Head in carrying out village development in Bipolo Village and Oeteta Village. The method used in this research is empirical juridical and statutory and primary data and secondary data are used as types of data sources. The research results show that the function of the Village Head is in carrying out village development in Bipolo Village and Oeteta Village. Bipolo village is running quite well because some village development has been realized, but the community is not firm enough to fully support the implementation of village development. Oeteta Village is going quite well because all village development activities are still in the planning stage which will be implemented in 2023. Then, there are two inhibiting factors in implementing the duties and functions of the Bipolo and Oeteta village heads in implementing village development, namely human resources and facilities and infrastructure, which has not been effective in supporting the implementation of village development through increasing the economic, educational and health needs of the community. So researchers need to make collaborative efforts between the community and the village government to implement development in each village. There is awareness of bipolo and oeteta village heads in their duties and functions to prioritize the needs of local communities so that village development can run according to established plans. There is awareness of the village head and village officials to continue to supervise the implementation of village development through all village consultation proposals based on meetings to submit proposals which must be prioritized so that they can be implemented every year.